pH, Conductivity and Buffer Capacity of Six Iranian Wood Species - Sadeghifar, Hasan; Veisi, Ramin; Einollahi, Yashar; Seifollahi, Javad; Ghaffar Ebadi, Abdol (Asian Journal of Chemistry, 2010)
The pH, conductivity and buffer capacity of wood and bark of six Iranian woods investigated. The mean pH values of Fagus orientalis and Acer laetum, Alnus subcordata are about 7. The mean pH values of Quercus castaneaefolia and Carpinus betulus are about 5.0-5.5 in different part of stem. Parotia persica has lowest pH less than 5. Buffer capacity values of Acer laetum is more than 0.45 and for other woods are less than 0.4. Mean pH for each six tree bark is higher than stem pH. Bark pH for Acer laetum, Fagus orientalis and Alnus subcordata are ca. 7 and for other woods are ca. 5. Acer laetum has high conductivity and buffer capacity. Quercus castaneaefolia has minimum conductivity and buffer capacity.